Digitalisasi Sistem Informasi Akuntansi Terhadap Praktik Keberlanjutan UMKM - Sifa’un Nadhifah; Renata Triyaliska; Citra Dwi Ardita; Erna Chotidjah Suhatmi (Universitas Duta Bangsa Surakarta, 2025)
Digitalization of AIS (Accounting Information Systems) plays an important role in supporting the sustainability of MSMEs in Indonesia. This study aims to investigate the impact of digital AIS implementation on operational efficiency and managerial decisions of MSMEs, as well as to identify the main obstacles in the digitalization process. The method applied is literature analysis from various reliable scientific sources. The implementation of digital AIS improves operational efficiency, accelerates services, reduces recording errors, and strengthens the basis for decision-making. Obstacles as high costs, lack of technological infrastructure, low digital capabilities, and resistance to change still hinder maximum implementation. Key supporting elements include understanding of technology, skilled labor, adequate infrastructure, and government regulations. This study concludes that digitalization of AIS can improve MSME sustainability practices in economic, social, and environmental aspects, as long as it is supported by a strategic and collaborative approach.